An Investigation on Local Shearing Mechanisms of Irregular Dentate Rock Joints Using the PFC. (22nd June 2022) - Huan, Jiuyang; He, Mingming; Zhang, Zhiqiang; Hu, Mengdie
Abstract : Joint surfaces are widely distributed in natural rock mass, and their shear mechanical properties play an important role in determining the safety and stability of rock mass. Previous studies rarely discussed the contribution degree of different joint protrusions to resisting shear stress. In this study, seven irregular dentate joint profiles were proposed to represent the geometric morphology of natural joints. Joint samples were subjected to direct shear tests under constant normal stress using the particle flow code (PFC). First, the reliability of the research scheme was verified by routine test results. Secondly, based on the microcrack tracking module and the force chain analysis, the local failure modes of the joint sample after and during the shearing process are discussed in detail. The relationship between the shear stress and the number of microcracks was studied. Finally, based on the measuring circle function, the variation law of the mean stress at different joint protrusions during the shearing process was tracked. The maximum stress of each protrusion before the shear stress peak was introduced to quantitatively describe the contribution of local protrusions to shear stress. There was an important link between the size of the protrusion and the stress it can withstand. During the shearing process, the local shearing mechanism of the joint surface is controlled by the distribution of joint protrusions. The research results of this paper can provide a good idea for the follow-up joint surface research.